2022
DOI: 10.3390/ma15072371
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties, Crack Width, and Propagation of Waste Ceramic Concrete Subjected to Elevated Temperatures: A Comprehensive Study

Abstract: Waste ceramic concrete (WOC) made from waste ceramic floor tiles has several economic and environmental benefits. Fire is one of the most common disasters in buildings, and WOC is a brittle construction material; therefore, the mechanical properties of WOC structures under high temperatures should be considered. According to previous studies, hybrid fiber can further reduce damage to concrete under high temperatures. Meanwhile, crack width and propagation are among the key characteristics of concrete materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In order to calculate the fitting parameters, these nonlinear models are generally converted into linear regression models. The multiple linear regression is often used to predict the compressive and tensile strength of concrete [ 26 ]. Taking the power function model as an example, the linear regression equation for this model can be expressed as where is the measured compressive strength of time , is the coefficient matrix of this linear regression equation.…”
Section: Regression Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to calculate the fitting parameters, these nonlinear models are generally converted into linear regression models. The multiple linear regression is often used to predict the compressive and tensile strength of concrete [ 26 ]. Taking the power function model as an example, the linear regression equation for this model can be expressed as where is the measured compressive strength of time , is the coefficient matrix of this linear regression equation.…”
Section: Regression Analysis Methodsmentioning
confidence: 99%
“…They found that the relationship between reflection loss and compressive strength is independent of curing temperature. Najm et al [ 25 , 26 ] studied the colour and strength change of the sustainable concrete containing waste ceramic and hybrid fibre in ambient and elevated temperatures. It was found that the appearance of colour alteration usually coincided with the onset of a significant strength loss due to elected temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Basic research should be prioritized in order to minimize the cost and increase the workability of geopolymers. Based on fundamental research, embarking on solid wastes to explore the preparation of varied characteristics of geopolymers in order to produce high-value-added application domains should be one of the primary paths of future geopolymer research development [ 1 , 266 , 267 , 268 , 269 , 270 ].…”
Section: Challenges For Solid Wastes In Geopolymermentioning
confidence: 99%
“…In addition to per reported documents, concrete incorporating up to 50% fine ceramic aggregates as natural aggregates resulted in higher compressive strength and durability performance. Moreover, the use of up to 40% ceramic waste as coarse aggregates in high-performance concrete revealed a significant reduction in autogenous shrinkage [17,18]. Rubber was used for the partial replacement of fine aggregate up to 7.5% as replacement content which led to a decline in the concrete's desired strength; accordingly, the compressive strength decreased as the rubber incorporation range increased.…”
Section: Introductionmentioning
confidence: 99%